2017
DOI: 10.1155/2017/4936490
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Car‐Following Model Accounting for Impact of Strong Wind

Abstract: In order to investigate the effect of strong wind on dynamic characteristic of traffic flow, an improved car-following model based on the full velocity difference model is developed in this paper. Wind force is introduced as the influence factor of car-following behavior. Among three components of wind force, lift force and side force are taken into account. The linear stability analysis is carried out and the stability condition of the newly developed model is derived. Numerical analysis is made to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…When the wind becomes great enough, drivers have to adjust the speed of their vehicles to avoid the impact of it. On the grounds of the analysis of the impact of strong wind in a car-following model [45], we further explore the impact of wind in a lattice model. Moreover, the effect of optimal estimation of flux difference integral [46] has not been researched in the wind.…”
Section: Methods: the Modified Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…When the wind becomes great enough, drivers have to adjust the speed of their vehicles to avoid the impact of it. On the grounds of the analysis of the impact of strong wind in a car-following model [45], we further explore the impact of wind in a lattice model. Moreover, the effect of optimal estimation of flux difference integral [46] has not been researched in the wind.…”
Section: Methods: the Modified Modelmentioning
confidence: 99%
“…Kwon [44] reported that traffic accidents may occur due to the wind force. The effect of strong wind was studied by Liu [45]. The research results of a study applying a car-following model suggest that strong wind is advantageous for the stability of traffic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of recent studies presents how local weather conditions affect real-time traffic flows both spatially and temporally [10]. A completely different idea to investigate the topic next, the authors have been checking the effect of strong wind on dynamic characteristic of traffic flow to improve car-following model and explore fuel consumption [11].…”
Section: Road Traffic Conditionsmentioning
confidence: 99%
“…Wind is a good example in that this factor (like speed) has an additional important attribute, which is direction. Liu & et al uses three components of wind force, lift force and side force preparing improved car-following model and during fuel consumption analyses [11] [20]. Related to the wind and visibility factors but not obvious for the population of moderate zones is the phenomenon of sandstorms.…”
Section: Weather Conditionsmentioning
confidence: 99%
“…Such mixed traffic flow is likely to be realistic in the near future and its string stability becomes importation topic in traffic flow theory. Many studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have been conducted to analyze the impacts of CACC vehicles on traffic flow stability. From the perspective of analytical investigation, we found that there are two major approaches for analytical investigation of string stability of the mixed traffic flow in the previous studies.…”
Section: Introductionmentioning
confidence: 99%